1993
DOI: 10.1159/000236478
|View full text |Cite
|
Sign up to set email alerts
|

Sequence Polymorphisms of cDNA Clones Encoding the Mite Allergen <i>Der </i><i>p</i> I

Abstract: Sequence information has been obtained from 5 cDNA clones encoding the major house dust mite allergen Der p I, including one which codes for the full length preproenzyme form of the molecule. All translated sequences were unique with 1–3 differences between each clone. 4/5 of the substitutions found were to residues found in Der f l and two positions had a substitution in more than one clone. The polymorphisms included residues already described to be in T cell epitopes, so as well as being necessary to consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
61
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(70 citation statements)
references
References 13 publications
9
61
0
Order By: Relevance
“…The amino acid sequence of the pre-precursor form of Der p 1 (pro-Der p 1) 3 clone selected for expression was identical with Der p 1.0102 (18), which was reported previously as "clone (c)" by Chua et al (51), except for one residue (Ϫ95) in the signal sequence (44). For the immunization of mice, we used a recombinant mutant Der p 1 designated Der p 1-N52Q, which has the same m.w.…”
Section: Recombinant Der Psupporting
confidence: 59%
“…The amino acid sequence of the pre-precursor form of Der p 1 (pro-Der p 1) 3 clone selected for expression was identical with Der p 1.0102 (18), which was reported previously as "clone (c)" by Chua et al (51), except for one residue (Ϫ95) in the signal sequence (44). For the immunization of mice, we used a recombinant mutant Der p 1 designated Der p 1-N52Q, which has the same m.w.…”
Section: Recombinant Der Psupporting
confidence: 59%
“…3. Since polymorphism is found in other house dust mite allergens, Der p 1 [19] and Der f 2 [11,13], the amino acid variation in the reported sequences might be due to polymorphism. To examine the possibility, we tried to clone other-type Der f 3 cDNAs by PCR.…”
Section: Polymorphism Older F3mentioning
confidence: 90%
“…The group 1 allergens, like other cysteine proteases, have 19-residue leader and a 79-residue proenzyme sequences [79, 86, 89]. The Der p 1 allergen isolated from mites was first shown to have cysteine protease activity [90, 91]but further study revealed that it exhibits a unique mixed cysteine and serine protease activity, even though it only has one active site [92].…”
Section: Group 1 Allergensmentioning
confidence: 99%